Comparative Study on Microstructure and Corrosion Resistance of Mg-Al Based Alloy with Mn and Sr Addition - Xu1, Tiancai; Peng1, Xiaodong; Zhang1, Bao; Jiang1, Junwei; Zhang1, Xi; Chen1, Yuanfang (Asian Journal of Chemistry, 2014)
Magnesium alloys, including Mg-3Al-0.5Mn (AM30), Mg-3Al-0.5Sr (AJ30) and Mg-3Al-0.5Mn-0.5Sr (AMJ300), were designed and prepared in vacuum induction furnace under controlled argon atmosphere. The effects of minor Sr and Mn addition on the microstructure and corrosion resistance of the Mg-3Al (wt.%) alloy were investigated by light and scanning electron microscopy, energy dispersive spectrometry, X-ray diffraction and electrochemical testing. The results indicate that AM30 alloy is composed of a-Mg and Al11Mn14 phases, whereas the AJ30 alloy consists of a-Mg, Al4Sr and Mg17Sr2 phases. Beyond above phases, AMJ300 alloy is composed of Mn phase. The Sr addition refined the as-cast grain structure of Mg-3Al alloy and the grain refining effect of Sr is more pronounced than Mn addition at the same level. However, the addition of Sr is not as effective as the simultaneous addition of Sr + Mn for the refinement of grains. Compared to Sr, Mn improved the corrosion resistance of binary Mg-Al. Due to its smallest corrosion current density and corrosion rate, the corrosion resistance of AM30 alloy is proved the best. The highest corrosion rate was observed for AJ30 alloy. The main solid corrosion products were Mg(OH)2.